Public attitudes and perceptions of wind energy development within the Rolling Plains and Breaks ecological region - Tucker, Terry (Kansas State University, 2016)
The Great Plains possesses one of the best sources of wind energy in North America. Based upon the need to diversify energy production domestically, wind energy’s future in both the immediate and long term should be dynamic. The success of wide scale development of this potential will be largely determined by the perceptions of local residents, who are most affected by the siting and design of wind energy projects. Currently, regulation of this natural resource is left largely to state and county governments. A majority of these entities in the Great Plains region have no regulations governing wind energy development or employ a patchwork of "borrowed" codes from across the nation. The system of regulation of natural resources by political boundary is archaic. It fails to recognize that there are high degrees of correlation between social, economic, and natural resources without respect for artificial political boundaries. This study is the first in the Great Plains to examine public attitudes toward the development of wind energy and its relationship to the landscape based upon ecological regions rather than political boundaries. The analysis of collected data will provide a useful tool for local planners, policy makers, and the general public in understanding the prevalent issues involved with wind energy development in this region.
Keywords: Wind energy development; Public attitudes and perceptions of wind energy development; Aesthetics of wind energy; Nimbyism and wind energy development; Ecoregion resource regulation; Environmental design